(untitled) (Metallurgy and Foundry Engineering, 2007)
N An attempt to implement the fuzzy logic to quick and economic analysis of the mixing process in two component system (alumina powder-ceramic fibres) was made. An experiment with composites made by the powder metallurgy method and the determination of its selected properties were carried out. To obtain samples cold moulding and coextrusion were used. The forming process was made with constant parameters of mixing and forming. The influence of fibrę volume fraction in the matrix on the selected properties and the microstructure of the product was investigated. Experimental results and experts’ knowledge were the input information for numerical computations and were represented by linguistic variables, fuzzy sets and fuzzy rules. Obtained or estimated in such way information from the technical point of view must be treated as an incomplete and uncertain knowledge. It means the mathematical description verified by experiments is not available. This knowledge was used to analyse the mixing parameters by the fuzzy logic. To implement inference the Fuzzy Logic Toolbox from Matlab package was used.